Numerical assessment of ultimate strength of severe corroded stiffened plates. (1st August 2018) - Woloszyk, K.; Kahsin, M.; Garbatov, Y.
Highlights: Corrosion degradation effect on the ultimate strength of stiffened plates is analyzed. Different factors governing structural behavior are investigated. A sensitivity analysis with respect to governing parameters is performed. The procedure avoids using of a pitted surface leading to fast and practical approach. Abstract: The objective of this work is to investigate numerically (using the non-linear FEM and the approach stipulated by the Common Structural Rules) the severe nonuniform corrosion degradation effect on the ultimate strength of stiffened plates and compare the results to the already published experimental works. Different factors governing structural behavior of corroded stiffened plates are investigated, such as corrosion degradation level, material properties, initial imperfections and boundary conditions. The numerically estimated ultimate strength demonstrated to be very close to those observed during the experimental test. A sensitivity analysis with respect to the most important governing parameters of the numerical estimation of the ultimate strength is also performed and several conclusions are derived. The applied calculation procedure avoids using of a pitted surface of the corroded plates and instead of that an equivalent thickness is applying leading to a relatively fast and practical approach for ultimate strength assessment of corroded stiffened plates.